Mandatory Multilateralism. Issue 2 (9th April 2019) - Criddle, Evan J.; Fox-Decent, Evan
Abstract: This Article challenges the conventional wisdom that states are always free to choose whether to participate in multilateral regimes. International law often mandates multilateralism to ensure that state laws and practices are compatible with sovereign equality and joint stewardship. The Article maps mandatory multilateralism's domain, defines its requirements, and examines its application to three controversies: the South China Sea dispute, the United States' withdrawal from the 2015 Paris Agreement, and Bolivia's case against Chile in the International Court of Justice.